Sarcopenia and the rate of change of the neutrophil/lymphocyte ratio as predictors of pembrolizumab efficacy in advanced urothelial carcinoma. Issue 5 (21st February 2022) - Fukata, Satoshi; Mizutani, Keisuke; Yamamoto, Shinkuro; Kuno, Takahira; Fukuhara, Hideo; Ashida, Shingo; Karashima, Takashi; Inoue, Keiji
Abstract : The objective was to evaluate the usefulness of sarcopenia and the neutrophil/lymphocyte ratio (NLR) as therapeutic efficacy predictors in patients who received pembrolizumab after platinum-based chemotherapy for advanced urothelial carcinoma (aUC). Forty-four patients with aUC were enrolled. Patients' background characteristics and clinical factors, the skeletal muscle index, and the psoas muscle index were evaluated. The NLR before and during treatment was calculated, and the rate of change of NLR was calculated. The median age was 70 years; the follow-up period was 13.2 months. The response rate was 54%. The nonresponding group had significantly more sarcopenia cases ( P = 0.007) and a high rate of change of NLR ( P = 0.0076). Progression-free survival (PFS) was significantly shorter in the group with sarcopenia ( P = 0.002). Both PFS and overall survival were significantly shorter with an NLR rate of change greater than or equal to 1 ( P = 0.001 and P = 0.002). On multivariate analysis, the presence of immune-related adverse events [hazard ratio (HR), 0.3723; 95% confidence interval (CI), 0.14–0.97; P = 0.04] and the NLR rate of change (HR, 3.986; 95% CI, 1.01–15.70; P = 0.048) were independent predictors of PFS. Sarcopenia and the rate of change of NLR appear to be useful as predictors of pembrolizumab efficacy in aUC.